Comparative Analyses of the Digestive Tract Microbiota of New Guinean Passerine Birds - Bodawatta, Kasun H.; Sam, Katerina; Jønsson, Knud A.; Poulsen, Michael (Frontiers in Microbiology, 2018)
The digestive tract microbiota (DTM) plays a plethora of functions that enable hosts to exploit novel niches. However, our understanding of the DTM of birds, particularly passerines, and the turnover of microbial communities along the digestive tract are limited. To better understand how passerine DTMs are assembled, and how the composition changes along the digestive tract, we investigated the DTM of seven different compartments along the digestive tract of nine New Guinean passerine bird species using Illumina MiSeq sequencing of the V4 region of the 16S rRNA. Overall, passerine DTMs were dominated by the phyla Firmicutes and Proteobacteria. We found bird species-specific DTM assemblages and the DTM of different compartments from the same species tended to cluster together. We also found a notable relationship between gut community similarity and feeding guilds (insectivores vs. omnivores). The dominant bacterial genera tended to differ between insectivores and omnivores, with insectivores mainly having lactic acid bacteria that may contribute to the breakdown of carbohydrates and bacterial diversity generally lower than for omnivores. Omnivorous DTMs were more diverse than insectivores and dominated by bacterial phyla of Proteobacteria and Tenericutes. These bacteria may contribute to nitrogen metabolism, and the diverse omnivorous DTMs may allow for more flexibility with varying food availability as these species have wider feeding niches. In well-sampled omnivorous species, the dominant bacterial genera changed along the digestive tracts, which was less prominent for insectivores. In conclusion, the DTMs of New Guinean passerines seem to be species specific and, at least in part, be shaped by bird diet. The sampling of DTM along the digestive tract improved capturing of a more complete set of members, with implications for our understanding of the interactions between symbiont and gut compartment functions.